2014
DOI: 10.1200/jco.2014.32.4_suppl.38
|View full text |Cite
|
Sign up to set email alerts
|

Predicting progression in patients followed with active surveillance for low-risk prostate cancer.

Abstract: 38 Background: Due to the inability to predict progression and need for treatment, patients with low-risk prostate cancer (LRPC) managed by active surveillance (AS) are subjected to repeated biopsies and their possible complications. We developed a nomogram predicting the risk of progression in patients on AS for LRPC. Methods: A retrospective review of all patients enrolled in an AS program at Memorial Sloan-Kettering Cancer Center (MSKCC) between 1993 and 2012 was conducted. Demographic, clinical, and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The extent of cancer on biopsy such as number of positive cores, cancer length and/or percentage of core involvement were also shown in the majority of studies to be important predictors of disease progression or the probability of remaining on AS (5, 9, 11, 14, 19, 21, 24, 25, 27, 32, 35, 40, 4547). Bul et al (19) showed that the strongest predictors for short-term biopsy reclassification (> 2 positive cores or GS >6 at repeat biopsy) were PSA density and the number of positive cores (2 versus 1).…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of cancer on biopsy such as number of positive cores, cancer length and/or percentage of core involvement were also shown in the majority of studies to be important predictors of disease progression or the probability of remaining on AS (5, 9, 11, 14, 19, 21, 24, 25, 27, 32, 35, 40, 4547). Bul et al (19) showed that the strongest predictors for short-term biopsy reclassification (> 2 positive cores or GS >6 at repeat biopsy) were PSA density and the number of positive cores (2 versus 1).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Bul et al (19) showed that the strongest predictors for short-term biopsy reclassification (> 2 positive cores or GS >6 at repeat biopsy) were PSA density and the number of positive cores (2 versus 1). One recent study by Sternberg et al (21) created a nomogram for progression on AS including age, clinical stage, PSA, number of positive cores at diagnosis, percent of positive cores at diagnosis, and number of positive and negative biopsies to date. Another study by Iremashvili et al (45) created a nomogram using race, PSA density and the total number of positive cores on diagnostic and first repeat biopsy to predict the probability of no progression on 2 nd –4 th repeat biopsies.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In the literature, many articles found that maximum percent core involvement at diagnosis was associated with progression (23-26). Sternberg et al (27) and Iremashvili et al (28) created nomograms that include number of positive cores and percent of positive cores at diagnosis. However, disease progression and extent of cancer on biopsy are not associated significantly in some studies (29,30).…”
Section: Discussionmentioning
confidence: 99%